Tau leptonic branching ratios - BUSKULIC, D. (Institutional Knowledge at Singapore Management University, 1996)
A sample of 62249 τ-pair events is selected from data taken with the ALEPH detector in 1991, 1992 and 1993. The measurement of the branching fractions for τ decays into electrons and muons is presented with emphasis on the study of systematic effects from selection, particle identification and decay classification. The results obtained are: B e = 17.79±0.12(stat)±0.06(syst)(%) and Bμ = 17.31±0.11(stat)±0.05(syst)(%). Combined with the most recent ALEPH determination of the τ lifetime, these results provide a relative measurement of the leptonic couplings in the weak charged current for transverse W bosons: ${cal G}_{ώ}/{cal G}_{e}=1.0002pm 0.0051$ and ${cal G}_{∢u}/{cal G}_{u}=0.9943pm 0.0065$.